Gambaran Kepuasan Pasien Terhadap Pelayanan Kefarmasian pada Layanan Telemedisin Internal Apotek X di Kota Denpasar - Sanjaya, I Putu Maheswara Dharma; Apsari, Dewi Puspita; Tunas, I Ketut (Bali International University, 2025)
Background: Telemedicine services are consultation services with doctors where patients and doctors do not have to meet face to face to communicate with each other to discuss the health problems they are experiencing. In some telemedicine services such as internal telemedicine service, pharmacists only play a role in preparing drugs that have been prescribed by doctors as a result of discussions with previous patients. So that the pharmaceutical services received by patients are considered less than optimal. So it is necessary to know how patient satisfaction with pharmaceutical services has been received and how patients expect this service in the future Research Objectives: To determine patient satisfaction and expectations of pharmaceutical services in internal telemedicine services of pharmacy X. Method: This study uses a quantitative method, namely an observational with a cross-sectional . The measurement of the patient's expectations was carried out using a reality and expectation questionnaire that was given in pharmacy X Results: In the analysis of the gap between reality and expectations of 2 dimensions, namely: